Development of a Google Sites-Based Learning Medium for German Reading A2 on the Topic of Arbeitswelten - Devi Triana Purba; Ahmad Bengar Harahap (Program Studi Pendidikan Bahasa dan Sastra Indonesia, FKIP, Universitas Halu Oleo Kampus Bumi Tridharma Andounohu Kendari, Provinsi Sulawesi Tenggara – Indonesia, 2026)
This study aimed to develop a Google Sites-based learning medium for German Reading A2 on the topic Arbeitswelten. The study employed a Research and Development (R&D) method using the ADDIE model, which consists of five phases: Analysis, Design, Development, Implementation, and Evaluation. The needs analysis involved 28 fourth-semester students who had previously completed the German Reading A2 course, while the implementation phase involved 26 students from Class B of the 2025 batch who were taking the course. The learning materials were adapted from Netzwerk neu A2 and complemented with resources from the Goethe-Institut. The developed website integrates reading materials, vocabulary support, and Wordwall-based interactive exercises within a single web-based learning environment.The results showed that the material expert validation reached 87.5% (Good), while the media expert validation reached 92.5% (Very Good). Student responses indicated positive perceptions of the usability, design, learning materials, and overall learning experience provided by the website. Based on these findings, it can be concluded that the developed Google Sites-based learning medium is feasible for use in German Reading A2 instruction on the topic Arbeitswelten.